Superhard superconductive B-C-N superhard material and preparation method thereof

By constructing a three-dimensional interpenetrating composite structure of nanotwinned diamond and cubic boron nitride and a BCN gradient transition layer in the superhard and superconducting BCN superhard material, the problems of weak interfacial bonding and superconducting phase decomposition when traditional superhard materials are combined with superconducting phases are solved, achieving a combination of high superhardness and stable superconductivity, and improving the fracture toughness and superconducting performance of the material.

CN121673053AInactive Publication Date: 2026-03-17JILIN INST OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511965836.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-24
Publication Date
2026-03-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing technologies cannot simultaneously achieve high hardness and stable superconductivity in a single material system. When traditional superhard materials are simply combined with superconducting phases, there are problems such as weak interfacial bonding and easy decomposition of the superconducting phase under high temperature and high pressure conditions.

Method used

Superhard and superconducting magnesium diboride was prepared by using superhard and superconducting BCN material, forming a three-dimensional interpenetrating composite structure by nanotwinned diamond and cubic boron nitride, and constructing a BCN ternary gradient transition layer at the interface. Combined with electrostatic self-assembly and precursor infiltration method, superconducting magnesium diboride was prepared.

Benefits of technology

This achievement realizes the efficient synergy between ultrahardness and superconductivity, improving the fracture toughness and superconductivity of the material, and enabling the material to exhibit excellent service performance in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a superhard superconductive B-C-N superhard material and a preparation method thereof, and belongs to the technical field of superhard materials, the superhard material comprises a three-dimensional interpenetrating composite structure composed of a superhard skeleton and a superconductive phase filled in the pores of the superhard skeleton; the superhard framework comprises a matrix formed by nano-twin diamond and lamellar cubic boron nitride embedded in the matrix, and a B-C-N ternary gradient transition layer exists at the interface of the nano-twin diamond and the cubic boron nitride area; the superconducting phase is magnesium diboride; the Vickers hardness of the superhard material ranges from 75.2 GPa to 82.1 GPa, and the superconducting transition temperature of the superhard material ranges from 35.8 K to 37.1 K; the mechanical property of a superhard material and the functional property of a superconducting material are perfectly fused into a whole, a comprehensive solution capable of replacing a traditional single-function material is provided, and the core problems that in the prior art, functions and performance are difficult to consider, and the service reliability of the material in an extreme environment is insufficient are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of superhard materials technology, and in particular to superhard and superconducting BCN superhard materials and their preparation methods. Background Technology

[0002] Superhard materials, represented by diamond and cubic boron nitride, occupy an important position in industrial fields such as machining, mining, and precision manufacturing due to their extremely high hardness, excellent wear resistance, and stable chemical properties. Among them, diamond is the hardest known material, but it easily reacts with iron group metals under high-temperature conditions, which severely limits its application in steel processing. Cubic boron nitride is second only to diamond in hardness, and also has better thermal stability and chemical inertness to iron, thus becoming a hot research material in this field.

[0003] Meanwhile, superconducting materials such as Nb-Ti, Nb3Sn, and MgB2 exhibit zero resistance and perfect diamagnetism under specific low-temperature conditions, thus possessing significant application value in fields such as nuclear magnetic resonance imaging, high-energy physics experiments, and power transmission. Among them, MgB2 is considered a promising mid-temperature superconducting material due to its significant advantages, including a high superconducting transition temperature, simple composition, and low cost.

[0004] As modern industry and technology expand into more extreme and complex environments, increasingly stringent requirements are being placed on the comprehensive performance of materials in applications such as mechanical systems in strong magnetic fields, wear-resistant components of high-precision quantum devices, and the internal structures of nuclear fusion devices. Traditional materials with single properties are no longer sufficient to meet these demands. There is an urgent need in this field for an integrated superhard and superconducting material that can simultaneously possess both extremely high mechanical load-bearing capacity and lossless conductivity. However, superhard materials are typically insulators or wide-bandgap semiconductors, while superconducting phases require specific metallic bonding and electronic structures. These two materials differ fundamentally in their crystal structure and bonding properties. Therefore, developing a single material system that combines both superhard and superconducting properties has become a significant technological challenge.

[0005] Currently, common technical approaches often employ the mechanical mixing and composite of superconducting powders and superhard materials. However, this method has significant technical limitations. First, under the high-temperature and high-pressure process conditions necessary for the sintering of superhard phases, most superconducting phases undergo structural decomposition or harmful side reactions with the matrix, leading to severe degradation or even loss of their superconducting properties. Second, the interfacial bonding strength formed by mechanical mixing is low, making it prone to becoming crack initiation points under stress, thus impairing the overall mechanical properties and reliability of the material.

[0006] In summary, there is a lack of novel materials and their preparation methods that can effectively integrate superhardness and superconductivity and possess a stable microstructure. Summary of the Invention

[0007] The purpose of this invention is to provide an ultrahard and superconducting BCN superhard material and its preparation method, so as to solve the technical problem that existing technologies cannot simultaneously achieve high ultrahardness and stable superconductivity in a single material system, and to overcome the technical bottlenecks that exist when traditional superhard materials are simply combined with superconducting phases, such as weak interfacial bonding, easy decomposition of superconducting phases under high temperature and high pressure conditions, and difficulty in synergistic control of macroscopic properties of materials.

[0008] To achieve the above objectives, the present invention provides the following solution:

[0009] The key to the superhard and superconducting BCN superhard material lies in the fact that the superhard material comprises a three-dimensional interpenetrating composite structure consisting of a superhard framework and a superconducting phase filling the pores of the superhard framework; the superhard framework comprises a matrix composed of nanotwinned diamond and lamellar cubic boron nitride embedded in the matrix, and a BCN ternary gradient transition layer exists at the interface between the nanotwinned diamond and the cubic boron nitride regions; the superconducting phase is magnesium diboride; the Vickers hardness of the superhard material is 75.2 GPa to 82.1 GPa, and the superconducting transition temperature is 35.8 K to 37.1 K.

[0010] A method for preparing the above-mentioned superhard material, the key feature of which is that it includes the following steps:

[0011] S1. Preparation of ultra-hard framework precursor: Onion carbon nanoparticles and hexagonal boron nitride microsheets modified with BCN gradient layer are used as raw materials. Through electrostatic self-assembly process, the onion carbon nanoparticles are coated on the surface of hexagonal boron nitride microsheets to form composite precursor powder; wherein, the mass ratio of onion carbon nanoparticles to hexagonal boron nitride microsheets modified with BCN gradient layer is (6~7):3.

[0012] S2. High temperature and high pressure sintering: The above composite precursor powder is sintered under high temperature and high pressure to transform the above onion carbon nanoparticles into the above nanotwinned diamond, and to transform the above hexagonal boron nitride microsheets into the above cubic boron nitride, thereby obtaining an ultrahard skeleton with micro-nano-level interconnected pores.

[0013] S3. Introduction of superconducting phase: Using the precursor infiltration method, a slurry prepared by magnesium powder and amorphous boron powder is filled into the pores of the above-mentioned superhard skeleton. Under argon protection, heat treatment is carried out to generate magnesium diboride superconducting phase in situ, thereby obtaining the above-mentioned superhard material; the mass ratio of the above slurry to the superhard skeleton is (1.0~1.5):1.

[0014] Furthermore, in step S1, the preparation method of the hexagonal boron nitride microsheet modified with the BCN gradient layer is as follows:

[0015] Surface-activated hexagonal boron nitride microsheets were reacted with sucrose and boric acid under hydrothermal conditions at 160℃~200℃ for 10h~15h, and then heat-treated at 700℃~900℃ for 1h~3h under argon protection to form a core-shell structure, thus obtaining the above-mentioned hexagonal boron nitride microsheets modified with BCN gradient layer.

[0016] Furthermore, the surface activation method for hexagonal boron nitride microsheets is as follows: hexagonal boron nitride microsheets with a particle size of 1μm to 5μm are dispersed in deionized water and irradiated sequentially with ultraviolet light sources with wavelengths of 185nm and 254nm for 0.5h to 2h under an ozone atmosphere. After treatment, the microsheets are centrifuged and dried to obtain the above-mentioned surface-activated hexagonal boron nitride microsheets with a surface rich in -B-OH and -NH active functional groups.

[0017] Furthermore, in step S1, the above-mentioned onion carbon nanoparticles are cyclic carbon nanoparticles prepared by a carbide etching method.

[0018] Specifically, the process of the above-mentioned carbide etching method is as follows: under argon protection, the nano-carbide reacts with halogen gas at a reaction temperature of 700℃~900℃ for 30min~120min. After the reaction is completed, it is naturally cooled to room temperature to obtain a crude product. After acid washing, washing and drying, the above-mentioned cyclic carbon nano-onion is obtained. The above-mentioned nano-carbide is titanium carbide or silicon carbide. The above-mentioned halogen gas is chlorine or bromine vapor.

[0019] Specifically, in step S2, the conditions for the high-temperature and high-pressure sintering are a pressure range of 15 GPa to 18 GPa, a temperature of 1700℃ to 1850℃, and a sintering time of 5 min to 15 min.

[0020] Preferably, in step S3, the atomic ratio of magnesium powder to amorphous boron powder in preparing the above slurry is 1:2.

[0021] Furthermore, the precursor permeation method in step S3 specifically involves: under a vacuum of 1×10⁻⁶... -2 Pa ~ 1×10 -3 The above-mentioned ultra-hard skeleton was pretreated at 150℃~250℃ for 0.5h~1.5h; during infiltration, an argon pressure of 5MPa~15MPa was applied and the pressure was maintained for 20min~40min.

[0022] Furthermore, in step S3, the heat treatment conditions are as follows: first, the temperature is increased to 250℃ to 350℃ at a rate of 3℃ / min to 8℃ / min and held for 0.5h to 1.5h; then, the temperature is increased to 700℃ to 800℃ at a rate of 8℃ / min to 12℃ / min and held for 20min to 40min.

[0023] The present invention discloses the following technical effects:

[0024] The superhard and superconducting BCN superhard material and its preparation method provided by this invention, through the unique three-dimensional interpenetrating structure design of the superhard skeleton and superconducting wick and the gradient interface atomic-level stitching process, breaks through the technical bottleneck of existing technologies that cannot simultaneously achieve high superhardness and stable superconductivity in a single material system.

[0025] Specific technical effects include:

[0026] First, this invention achieves for the first time a highly efficient synergy between superhardness and superconductivity in a bulk material. Addressing the inherent contradiction in existing technologies where superhard materials are typically insulators while superconducting materials have poor mechanical properties, this invention designs a three-dimensional interpenetrating composite structure consisting of a superhard framework made up of nanotwinned diamond / cBN gradient heterostructures and superconducting channels filled with magnesium diboride. The material of this invention maintains its superhardness of over 75 GPa while achieving a superconducting transition temperature, fundamentally solving the technical problem in traditional material systems where superhardness equates to poor conductivity, and vice versa.

[0027] Secondly, this invention achieves atomic-level robust bonding at the heterogeneous interface through a BCN gradient transition layer. Addressing the weak interface problem caused by lattice mismatch and chemical differences between the nanotwinned diamond and cubic boron nitride phases, this invention creatively constructs a continuously varying compositional BCN ternary gradient transition layer at the interface using a combined hydrothermal-thermal treatment method. This transition layer achieves atomic-level bonding between diamond and cBN, improving the fracture toughness of the composite material by over 80% compared to traditional simple composite materials, effectively avoiding the brittle fracture problem common in superhard materials.

[0028] Third, the preparation process of this invention ensures the perfect formation and distribution of the superconducting phase in the ultrahard matrix. Addressing the technical challenges of the superconducting phase's easy decomposition under high temperature and high pressure conditions and its incompatibility with the ultrahard matrix, this invention develops a two-step preparation route: first building the matrix, then filling in the wick. Through precisely controlled precursor infiltration and stepwise heat treatment processes, a continuous and pure magnesium diboride superconducting phase is generated in situ in the matrix pores under relatively mild conditions, achieving a critical current density of 10. 5 A / cm 2 This method achieves a breakthrough in the production of superconducting functional units without compromising the structural integrity of the ultra-hard framework, thus solving the technological challenge of the survival of these units under extreme synthesis conditions.

[0029] Fourth, the material of this invention exhibits outstanding performance in extreme environments. This is thanks to the robust gradient interface and highly thermally conductive ultra-hard framework of this invention. After being treated at 1000℃, the material retains more than 94% of its hardness and can withstand severe thermal shock without cracking. This unique thermal stability and thermal shock resistance, combined with its ultra-hard and superconducting dual properties, makes this material irreplaceable in extreme conditions such as the inner wall materials of nuclear fusion devices and wear-resistant superconducting components in strong magnetic field environments.

[0030] In summary, this invention perfectly integrates the mechanical properties of superhard materials with the functional properties of superconducting materials, providing a comprehensive solution that can replace traditional single-function materials. It effectively solves the core problems in existing technologies, such as the difficulty in balancing function and performance and the insufficient reliability of materials in extreme environments. Detailed Implementation

[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0032] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included within the scope of this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0033] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0034] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0035] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0036] In this invention, the magnesium powder has a purity of 99.9% and comes from Beijing Hongyu New Materials Technology Co., Ltd.; the amorphous boron powder has a purity of 99.9% and comes from Zhejiang Yamei Nanotechnology Co., Ltd.; and the hexagonal boron nitride with a particle size of 1μm to 5μm has a purity of 99.9% and comes from Shanghai Pantian Powder Materials Co., Ltd., with the particle size being the average particle size indicated on commercially available hexagonal boron nitride products.

[0037] Example 1

[0038] This embodiment provides an ultrahard superconducting BCN superhard material, which comprises a three-dimensional interpenetrating composite structure consisting of an ultrahard framework and a superconducting phase filling the pores of the ultrahard framework; its ultrahard framework comprises a matrix composed of nanotwinned diamond and layered cubic boron nitride embedded in the matrix, and a BCN ternary gradient transition layer exists at the interface between the nanotwinned diamond and the cubic boron nitride regions; its superconducting phase is magnesium diboride.

[0039] The preparation steps of the superhard material in this embodiment include:

[0040] S1. Preparation of ultra-hard skeleton precursor:

[0041] S11. Preparation of onion carbon nanoparticles:

[0042] In a tube furnace, under argon protection, titanium carbide with an average particle size of 50 nm was reacted with chlorine gas of 99.9% purity at 800 °C for 60 min. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a crude product. After acid washing, washing and drying, cyclic carbon nanoparticles were obtained, namely onion carbon nanoparticle sample 1.

[0043] S12. Preparation of hexagonal boron nitride microsheets modified with BCN gradient layers:

[0044] S121. 1g of hexagonal boron nitride microsheets with a particle size of 3μm were dispersed in 200mL of deionized water and irradiated with ultraviolet light sources with wavelengths of 185nm and 254nm for 1h in an ozone atmosphere. After treatment, the microsheets were centrifuged and dried to obtain surface-activated hexagonal boron nitride microsheet sample 1.

[0045] S122. Surface-activated hexagonal boron nitride microsheet sample 1 was reacted with 0.5g sucrose and 0.3g boric acid at 180℃ for 12h under hydrothermal conditions, and then heat-treated at 800℃ for 2h under argon protection to form a core-shell structure, thus obtaining hexagonal boron nitride microsheet sample 1 modified with BCN gradient layer.

[0046] S13, Electrostatic self-assembly to form a composite precursor:

[0047] All the hexagonal boron nitride microsheet samples 1 modified with BCN gradient layer obtained in step S12 were redispersed in an ammonia solution with pH=10.5 and sonicated for 30 min to fully disperse and become negatively charged.

[0048] Meanwhile, the onion carbon nanoparticle sample 1 prepared in step S11 and all the hexagonal boron nitride microsheet sample 1 modified with BCN gradient layer were weighed at a mass ratio of 6.5:3 and dispersed in a dilute hydrochloric acid solution with pH=4.5. The mixture was ultrasonically treated for 30 min to ensure that it was fully dispersed and positively charged.

[0049] Under vigorous mechanical stirring at 550 r / min, the positively charged onion carbon suspension was slowly added dropwise to the negatively charged hexagonal boron nitride suspension.

[0050] After the addition is complete, continue stirring for 2 hours;

[0051] Finally, the composite powder was collected by vacuum filtration, washed with ethanol, and vacuum dried at 80°C for 6 hours to obtain the composite precursor powder.

[0052] S2, High-temperature and high-pressure sintering:

[0053] The obtained composite precursor powder was loaded into a tantalum tube and pre-pressed, then placed in the pyrophyllite assembly block of a six-sided press, the pressure chamber was closed, the pressure was applied to 16 GPa, and then the sample temperature was raised to 1800℃ by a graphite heater and sintered for 10 min to obtain an ultrahard framework with micro-nano-scale interconnected pores.

[0054] S3, Introduction of superconducting phase:

[0055] Magnesium powder and amorphous boron powder were precisely weighed at an atomic ratio of 1:2, mixed and ground with anhydrous ethanol, and prepared into a slurry.

[0056] The ultra-hard skeleton obtained in step S2 was placed in a vacuum furnace and evacuated to a vacuum level of 5 × 10⁻⁶ at 200°C. -3 Pa, and keep warm for 1 hour;

[0057] While maintaining a vacuum, the mass ratio of the above slurry to the ultra-hard skeleton is controlled at 1.2:1, and an argon pressure of 10 MPa is applied and maintained for 30 min.

[0058] Subsequently, the permeated sample was placed in a vacuum tube furnace and heated to 300°C at a rate of 5°C / min and held for 1 hour under the protection of high-purity argon. Then, it was heated to 750°C at a rate of 10°C / min and held for 30 minutes.

[0059] After the process is completed, the material is cooled in the furnace and then vacuum dried at 65°C for 2 hours to obtain a superhard material, which is designated as material sample 1.

[0060] Example 2

[0061] This embodiment provides an ultrahard superconducting BCN superhard material, which comprises a three-dimensional interpenetrating composite structure consisting of an ultrahard framework and a superconducting phase filling the pores of the ultrahard framework; its ultrahard framework comprises a matrix composed of nanotwinned diamond and layered cubic boron nitride embedded in the matrix, and a BCN ternary gradient transition layer exists at the interface between the nanotwinned diamond and the cubic boron nitride regions; its superconducting phase is magnesium diboride.

[0062] The preparation steps of the superhard material in this embodiment include:

[0063] S1. Preparation of ultra-hard skeleton precursor:

[0064] S11. Preparation of onion carbon nanoparticles:

[0065] In a tube furnace, under argon protection, silicon carbide with an average particle size of 40 nm was reacted with chlorine gas of 99.9% purity at 900 °C for 30 min. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a crude product. After acid washing, washing and drying, cyclic carbon nanoparticles were obtained, namely onion carbon nanoparticle sample 2.

[0066] S12. Preparation of hexagonal boron nitride microsheets modified with BCN gradient layers:

[0067] S121. 1g of hexagonal boron nitride microsheets with a particle size of 1μm were dispersed in 200mL of deionized water and irradiated with ultraviolet light sources with wavelengths of 185nm and 254nm for 0.5h in an ozone atmosphere. After treatment, the microsheets were centrifuged and dried to obtain surface-activated hexagonal boron nitride microsheet sample 2.

[0068] S122. Surface-activated hexagonal boron nitride microsheet sample 2 was reacted with 0.6g sucrose and 0.4g boric acid at 200℃ for 10h under hydrothermal conditions, and then heat-treated at 900℃ for 1h under argon protection to form a core-shell structure, thus obtaining hexagonal boron nitride microsheet sample 2 modified with BCN gradient layer.

[0069] S13, Electrostatic self-assembly to form a composite precursor:

[0070] All the hexagonal boron nitride microsheet samples 2 modified with BCN gradient layer obtained in step S12 were redispersed in an ammonia solution with pH=11 and ultrasonically treated for 25 min to make them fully dispersed and negatively charged.

[0071] Meanwhile, the onion carbon nanoparticle sample 2 prepared in step S11 and all the hexagonal boron nitride microsheet sample 2 modified with BCN gradient layer were weighed at a mass ratio of 7:3 and dispersed in a dilute hydrochloric acid solution with pH=5. The mixture was ultrasonically treated for 25 min to ensure that it was fully dispersed and positively charged.

[0072] Under vigorous mechanical stirring at 600 r / min, a positively charged onion carbon suspension was slowly added dropwise to a negatively charged hexagonal boron nitride suspension.

[0073] After the addition is complete, continue stirring for 1.5 hours;

[0074] Finally, the composite powder was collected by vacuum filtration, washed with ethanol, and dried under vacuum at 90°C for 4 hours to obtain the composite precursor powder.

[0075] S2, High-temperature and high-pressure sintering:

[0076] The obtained composite precursor powder was loaded into a tantalum tube and pre-pressed, then placed in the pyrophyllite assembly block of a six-sided press, the pressure chamber was closed, the pressure was applied to 18 GPa, and then the sample temperature was raised to 1850℃ by a graphite heater and sintered for 5 min to obtain an ultrahard framework with micro-nano-scale interconnected pores.

[0077] S3, Introduction of superconducting phase:

[0078] Magnesium powder and amorphous boron powder were precisely weighed at an atomic ratio of 1:2, mixed and ground with anhydrous ethanol, and prepared into a slurry.

[0079] The ultra-hard skeleton obtained in step S2 was placed in a vacuum furnace and evacuated to a vacuum of 1×10⁻⁶ at 250°C. -3 Pa, and keep warm for 0.5 hours;

[0080] While maintaining a vacuum, the mass ratio of the above slurry to the ultra-hard skeleton is controlled at 1.5:1, and an argon pressure of 15 MPa is applied and maintained for 20 min.

[0081] Subsequently, the permeated sample was placed in a vacuum tube furnace and heated to 350°C at a rate of 8°C / min and held for 0.5 h under the protection of high-purity argon gas. Then, it was heated to 800°C at a rate of 12°C / min and held for 20 min.

[0082] After the process is completed, the material is cooled in the furnace and then vacuum dried at 80°C for 1 hour to obtain a superhard material, which is designated as material sample 2.

[0083] Example 3

[0084] This embodiment provides an ultrahard superconducting BCN superhard material, which comprises a three-dimensional interpenetrating composite structure consisting of an ultrahard framework and a superconducting phase filling the pores of the ultrahard framework; its ultrahard framework comprises a matrix composed of nanotwinned diamond and layered cubic boron nitride embedded in the matrix, and a BCN ternary gradient transition layer exists at the interface between the nanotwinned diamond and the cubic boron nitride regions; its superconducting phase is magnesium diboride.

[0085] The preparation steps of the superhard material in this embodiment include:

[0086] S1. Preparation of ultra-hard skeleton precursor:

[0087] S11. Preparation of onion carbon nanoparticles:

[0088] In a tube furnace, under argon protection, titanium carbide with an average particle size of 60 nm was reacted with bromine vapor of 99.9% purity at 700 °C for 120 min. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain a crude product. After acid washing, washing and drying, cyclic carbon nanoparticles were obtained, namely onion carbon nanoparticle sample 3.

[0089] S12. Preparation of hexagonal boron nitride microsheets modified with BCN gradient layers:

[0090] S121. 1g of hexagonal boron nitride microsheets with a particle size of 5μm were dispersed in 200mL of deionized water and irradiated with ultraviolet light sources with wavelengths of 185nm and 254nm for 2h in an ozone atmosphere. After treatment, the microsheets were centrifuged and dried to obtain surface-activated hexagonal boron nitride microsheet sample 3.

[0091] S122. Surface-activated hexagonal boron nitride microsheet sample 3 was reacted with 0.4g sucrose and 0.2g boric acid at 160℃ for 15h under hydrothermal conditions, and then heat-treated at 700℃ for 3h under argon protection to form a core-shell structure, thus obtaining hexagonal boron nitride microsheet sample 3 modified with BCN gradient layer.

[0092] S13, Electrostatic self-assembly to form a composite precursor:

[0093] All the hexagonal boron nitride microsheet samples 3 modified with BCN gradient layer obtained in step S12 were redispersed in an ammonia solution with pH=10 and ultrasonically treated for 35 min to make them fully dispersed and negatively charged.

[0094] Meanwhile, the onion carbon nanoparticle sample 3 prepared in step S11 and all the hexagonal boron nitride microsheet samples 3 modified with BCN gradient layer were weighed at a mass ratio of 6:3 and dispersed in a dilute hydrochloric acid solution with pH=4. The samples were ultrasonically treated for 35 minutes to ensure that they were fully dispersed and positively charged.

[0095] Under vigorous mechanical stirring at 500 r / min, the positively charged onion carbon suspension was slowly added dropwise to the negatively charged hexagonal boron nitride suspension;

[0096] After the addition is complete, continue stirring for 2.5 hours;

[0097] Finally, the composite powder was collected by vacuum filtration, washed with ethanol, and vacuum dried at 70°C for 8 hours to obtain the composite precursor powder.

[0098] S2, High-temperature and high-pressure sintering:

[0099] The obtained composite precursor powder was loaded into a tantalum tube and pre-pressed, then placed in the pyrophyllite assembly block of a six-sided press, the pressure chamber was closed, the pressure was applied to 15 GPa, and then the sample temperature was raised to 1700℃ by a graphite heating element and sintered for 15 min to obtain an ultrahard framework with micro-nano-scale interconnected pores.

[0100] S3, Introduction of superconducting phase:

[0101] Magnesium powder and amorphous boron powder were precisely weighed at an atomic ratio of 1:2, mixed and ground with anhydrous ethanol, and prepared into a slurry.

[0102] The ultra-hard skeleton obtained in step S2 is placed in a vacuum furnace and evacuated to a vacuum of 1×10⁻⁶ at 150°C. -2 Pa, and keep warm for 1.5 hours;

[0103] While maintaining a vacuum, the mass ratio of the above slurry to the ultra-hard skeleton is controlled at 1.0:1, and an argon pressure of 5 MPa is applied and maintained for 40 min.

[0104] Subsequently, the permeated sample was placed in a vacuum tube furnace and heated to 250°C at a rate of 3°C / min and held for 1.5 h under the protection of high-purity argon gas. Then, it was heated to 700°C at a rate of 8°C / min and held for 40 min.

[0105] After the process is completed, the material is cooled in the furnace and then vacuum dried at 50°C for 3 hours to obtain a superhard material, which is designated as material sample 3.

[0106] Comparative Example 1

[0107] This comparative example provides a comparative material, the specific implementation of which is the same as in Example 1, except that: when preparing the ultrahard framework precursor, the step of constructing a BCN gradient transition layer on the hexagonal boron nitride microsheet is omitted, and the unmodified hexagonal boron nitride microsheet is directly composited with onion carbon nanoparticles.

[0108] The preparation process of this comparative material specifically includes the following steps:

[0109] S1. Preparation of comparative skeletal precursors:

[0110] S11. Preparation of onion carbon nanoparticles: Same as step S11 in Example 1.

[0111] S12. This comparative example directly uses hexagonal boron nitride microsheets with a particle size of 3 μm, without surface activation and BCN gradient layer modification, and is referred to as control hexagonal boron nitride microsheet sample 1.

[0112] S13, Electrostatic self-assembly to form a composite precursor:

[0113] All the comparative hexagonal boron nitride microsheet samples 1 from step S12 were redispersed in an ammonia solution with pH=10.5 and sonicated for 30 min to ensure full dispersion and negative charge.

[0114] Meanwhile, the onion carbon nanoparticle sample 1 prepared in step S11 and all the comparative hexagonal boron nitride microsheet sample 1 were weighed at a mass ratio of 6.5:3 and dispersed in a dilute hydrochloric acid solution with pH=4.5. The mixture was ultrasonically treated for 30 minutes to ensure that it was fully dispersed and positively charged.

[0115] Under vigorous mechanical stirring at 550 r / min, the positively charged onion carbon suspension was slowly added dropwise to the negatively charged hexagonal boron nitride suspension.

[0116] After the addition is complete, continue stirring for 2 hours;

[0117] Finally, the composite powder was collected by vacuum filtration, washed with ethanol, and vacuum dried at 80°C for 6 hours to obtain the comparative composite precursor powder.

[0118] S2, High-temperature and high-pressure sintering: Same as step S2 in Example 1, to obtain a comparative ultra-hard skeleton.

[0119] S3, Introduction of superconducting phase: Same as step S3 in Example 1, to obtain comparative material, denoted as material reference 1.

[0120] Comparative Example 2

[0121] This comparative example provides a comparative material, the specific implementation of which is the same as in Example 1, except that: when preparing the ultra-hard skeleton precursor, the electrostatic self-assembly process is omitted and replaced with a simple mechanical mixing process.

[0122] The preparation process of this comparative material specifically includes the following steps:

[0123] S1. Preparation of comparative skeletal precursors:

[0124] S11. Preparation of onion carbon nanoparticles: Same as step S11 in Example 1.

[0125] S12. Preparation of hexagonal boron nitride microsheets modified with BCN gradient layer: Same as step S12 in Example 1, to obtain hexagonal boron nitride microsheet sample 1 modified with BCN gradient layer.

[0126] S13. Preparation of composite precursors using a mechanical mixing method:

[0127] The onion carbon nanoparticle sample 1 prepared in step S11 and all the hexagonal boron nitride microsheet samples 1 modified with BCN gradient layer obtained in step S12 were weighed at a mass ratio of 6.5:3, placed together in a beaker, and anhydrous ethanol was added as a dispersion medium. The mixture was mechanically mixed in a ball mill at a speed of 300 r / min for 4 h.

[0128] Subsequently, the mixed powder was collected by vacuum filtration and dried under vacuum at 80°C for 6 hours to obtain the comparative composite precursor powder.

[0129] S2, High-temperature and high-pressure sintering: Same as step S2 in Example 1, to obtain a comparative ultra-hard skeleton.

[0130] S3, Introduction of superconducting phase: Same as step S3 in Example 1, to obtain comparative material, denoted as material reference 2.

[0131] Comparative Example 3

[0132] This comparative example provides a comparative material, the specific implementation of which is the same as that of Example 1, except that: in the superconducting phase introduction step, the stepwise heat treatment process is omitted, and the precursor slurry and the ultrahard skeleton are directly reacted and sintered at high temperature.

[0133] The preparation process of this comparative material specifically includes the following steps:

[0134] S1. Preparation of the ultra-hard skeleton precursor: Same as step S1 in Example 1.

[0135] S2, High-temperature and high-pressure sintering: Same as step S2 in Example 1, to obtain an ultra-hard skeleton.

[0136] S3. This comparative example uses the direct reaction sintering method to introduce the superconducting phase:

[0137] Magnesium powder and amorphous boron powder were precisely weighed at an atomic ratio of 1:2, and then mechanically dry-mixed with the ultrahard skeleton powder obtained in step S2 at a slurry to skeleton mass ratio of 1.2:1.

[0138] The mixed powder was pre-pressed into a tantalum tube and then placed in a pyrophyllite assembly block of a six-sided press. The pressure chamber was closed, and the pressure was applied to 5 GPa. The sample temperature was then directly raised to 800 °C using a graphite heating element and held for 30 min.

[0139] After the process is completed, the material is cooled in the furnace to obtain the control material, which is designated as material control 3.

[0140] Analysis and Testing

[0141] The material samples 1-3 prepared in Examples 1-3 and the material control samples 1-3 prepared in Comparative Examples 1-3 were subjected to comprehensive testing of superhardness and superconductivity.

[0142] All performance test samples were taken from standard blocks prepared in the same batch and polished before testing using a standardized metallographic sample preparation process to ensure comparability of results.

[0143] The specific process for metallographic sample preparation is as follows:

[0144] First, the sample surface was finely polished using diamond polishing paste with a particle size of 2.5 μm on an automatic polishing machine. Then, the surface was polished to a final mirror finish using diamond polishing paste with a particle size of 0.5 μm until no obvious scratches were observed on the surface under an optical microscope. Finally, the sample was cleaned in an ultrasonic cleaner for 10 minutes each with anhydrous ethanol and acetone to thoroughly remove any residual polishing agent and contaminants and ensure the test surface was clean.

[0145] I. Ultrahard Performance Test

[0146] The Vickers hardness of the material was measured using an ultramicro Vickers hardness tester under a load of 500 gf, with 10 points tested for each sample and the average value taken. Crack length was measured using the indentation method based on the hardness indentation, and the fracture toughness of the material was calculated. The wear rate was tested using a disc-to-disc friction and wear tester under a load of 10 N and a sliding distance of 100 m. The test results are shown in Table 1.

[0147] Table 1: Test Results of Superhardness Performance

[0148]

[0149] As shown in Table 1, the Vickers hardness of samples 1-3 of this invention reached over 75 GPa. Among them, sample 2 had the highest hardness, sample 3 had a relatively lower hardness but was still far superior to traditional superhard materials, and sample 1 had a hardness in between. The fracture toughness of all three samples was higher than 15 MPa·m. 1 / 2 The invention demonstrates excellent fracture resistance, and the extremely low wear rate proves that the sample of the invention has excellent wear resistance.

[0150] Material control 1, due to the omission of the BCN gradient transition layer, resulted in a fragile interface between the diamond and cBN phases, with a significant decrease in both hardness and fracture toughness. This verifies that the BCN gradient transition layer designed in this invention is crucial for achieving an atomically stitched interface with strong and tough bonding.

[0151] Material reference 2, due to mechanical mixing rather than electrostatic self-assembly, had uneven mixing of precursors, resulting in a less dense final skeleton structure. Although its hardness was higher than that of material reference 1, it was still much lower than that of the sample of the present invention. This shows that the electrostatic self-assembly process used in the present invention is indispensable for constructing a uniform and dense composite structure.

[0152] Material control 3, due to the introduction of the superconducting phase by direct reaction sintering, suffered from severe reaction conditions that damaged the structural integrity of the superhard framework, resulting in the worst mechanical properties and the lowest hardness. This proves that the mild precursor infiltration-assisted two-step heat treatment method used in this invention is the key to ensuring that the superhard framework is not damaged during the introduction of the superconducting phase.

[0153] II. Superconducting performance testing

[0154] Using a comprehensive physical property measurement system, the resistance-temperature curve of the material was measured by the four-wire method to determine the superconducting transition temperature (Tc); at 4.2 K, the upper critical field (Hc2) was determined by measuring the change in resistance with an external magnetic field; similarly, at 4.2 K and under self-field conditions, the critical current density (Jc) was measured by the transport current method. The test results are shown in Table 2.

[0155] Table 2: Superconducting performance test results

[0156]

[0157] As shown in Table 2, the superconducting transition temperatures of samples 1-3 of this invention are all above 35K. Among them, sample 3 exhibits the highest Tc, while sample 2 has a slightly lower Tc but is still within the excellent range. In addition, all three samples have high upper critical field and critical current density, indicating that the formed MgB2 superconducting phase is of high quality and has good connectivity.

[0158] Due to poor interfacial bonding, the superconducting phase MgB2 in material reference 1 had poor adhesion and continuity in the framework, resulting in a decrease in all superconducting properties, with Tc at 34.1 K.

[0159] Material reference 2 has a non-uniform framework structure, and the penetration and formation of the superconducting phase are also non-uniform, with weak connections. It not only has a lower Tc, but also the lowest Hc2 and Jc.

[0160] Material reference standard 3 failed to form a continuous and pure MgB2 superconducting phase due to improper synthesis process, and the material did not exhibit complete superconducting properties, proving that the superconducting phase introduction process used in this invention is the decisive factor in obtaining superconducting function.

[0161] III. Thermal stability and thermal shock resistance test

[0162] The samples were heated to 1000℃ under argon protection and held at that temperature for 1 hour. After cooling, the hardness retention rate was measured. The samples were then rapidly cooled from 1000℃ in room temperature water, and this cycle was repeated 5 times. The macroscopic morphology was observed and the hardness was measured to evaluate the thermal shock resistance. The results are shown in Table 3.

[0163] Table 3: Test Results of Thermal Stability and Thermal Shock Resistance

[0164]

[0165] As shown in Table 3, the material samples 1-3 of this invention exhibit excellent thermal stability and thermal shock resistance, with a hardness retention rate all exceeding 94%, and can withstand severe thermal shock. This is attributed to the robust gradient interface structure and highly thermally conductive ultra-hard skeleton of this invention. In contrast, the performance of each comparative sample significantly degraded under this stringent test due to their respective structural defects.

[0166] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. Superhard superconductive B-C-N superhard material, characterized in that, The superhard material comprises a three-dimensional interpenetrating composite structure composed of a superhard framework and a superconducting phase filled in the pores of the superhard framework; the superhard framework comprises a matrix composed of nanotwinned diamond and sheet-like cubic boron nitride embedded in the matrix, and at the interface between the nanotwinned diamond and the cubic boron nitride region, there is a layer of B-C-N ternary gradient transition layer; the superconducting phase is magnesium diboride; the Vickers hardness of the superhard material is 75.2GPa-82.1GPa, and the superconducting transition temperature is 35.8K-37.1K.

2. A method of producing superhard material as claimed in claim 1, characterised in that, The method comprises the following steps: S1, preparation of a superhard framework precursor: using onion carbon nanoparticles and B-C-N gradient layer modified hexagonal boron nitride microparticles as raw materials, the onion carbon nanoparticles are wrapped on the surface of the hexagonal boron nitride microparticles by an electrostatic self-assembly process to form a composite precursor powder; wherein the mass ratio of the onion carbon nanoparticles and the B-C-N gradient layer modified hexagonal boron nitride microparticles is (6-7):3; S2, high-temperature and high-pressure sintering: the composite precursor powder is sintered at high temperature and high pressure to make the onion carbon nanoparticles phase change into nanotwinned diamond, make the hexagonal boron nitride microparticles phase change into cubic boron nitride, and obtain a superhard framework with micro-nano interconnected pores; S3, introduction of a superconducting phase: a slurry prepared by mixing magnesium powder and amorphous boron powder is filled into the pores of the superhard framework by a precursor infiltration method, and heat treatment is performed under argon protection to generate magnesium diboride superconducting phase in situ, thereby obtaining the superhard material; the mass ratio of the slurry and the superhard framework is (1.0-1.5):

1.

3. The production method according to claim 2, characterized by, In step S1, the B-C-N gradient layer modified hexagonal boron nitride microparticles are prepared by the following method: The surface-activated hexagonal boron nitride microparticles are reacted with sucrose and boric acid under hydrothermal conditions at 160-200°C for 10-15h, and heat treated at 700-900°C for 1-3h under argon protection to form a core-shell structure, thereby obtaining the B-C-N gradient layer modified hexagonal boron nitride microparticles.

4. The production method according to claim 3, characterized by, The surface activation method of the hexagonal boron nitride microparticles is as follows: hexagonal boron nitride microparticles with a particle size of 1-5μm are dispersed in deionized water, and then irradiated with ultraviolet light sources with wavelengths of 185nm and 254nm in an ozone atmosphere for 0.5-2h, and then centrifuged and dried to obtain the surface-activated hexagonal boron nitride microparticles rich in -B-OH and -N-H active functional groups.

5. The production method according to claim 4, characterized by, In step S1, the onion carbon nanoparticles are annular carbon nanonions prepared by a carbide etching method.

6. The production method according to claim 5, wherein The specific process of the carbide etching method is as follows: under argon protection, nanocarbide is reacted with halogen gas at a reaction temperature of 700-900°C for 30-120min, and then naturally cooled to room temperature after the reaction to obtain a crude product, which is washed with acid, washed and dried to obtain the annular carbon nanonions; the nanocarbide is titanium carbide or silicon carbide; and the halogen gas is chlorine or bromine vapor.

7. The preparation method according to claim 2, characterized in that, In step S2, the high-temperature and high-pressure sintering is performed at a pressure of 15 GPa to 18 GPa, a temperature of 1700°C to 1850°C, and a sintering time of 5 min to 15 min.

8. The preparation method according to claim 2, characterized in that, In step S3, the slurry is prepared by mixing magnesium powder and amorphous boron powder at an atomic ratio of 1:

2.

9. The preparation method according to claim 2, characterized in that, The precursor infiltration method in step S3 is as follows: the precursor is infiltrated into the superhard skeleton under the conditions of a vacuum degree of 1×10 -2 Pa ~ 1×10 -3 Pa, and a temperature of 150℃ ~ 250℃ for 0.5h ~ 1.5h. During the infiltration, an argon pressure of 5MPa ~ 15MPa is applied, and the pressure is maintained for 20min ~ 40min.

10. The method of claim 2, wherein, In step S3, the heat treatment is performed by first heating at a rate of 3°C / min to 8°C / min to a temperature of 250°C to 350°C and maintaining the temperature for 0.5 h to 1.5 h, and then heating at a rate of 8°C / min to 12°C / min to a temperature of 700°C to 800°C and maintaining the temperature for 20 min to 40 min.